From nature to additive manufacturing: Biomimicry of porcupine quill. (15th November 2021) - Tee, Yun Lu; Maconachie, Tobias; Pille, Philip; Leary, Martin; Do, Truong; Tran, Phuong
Graphical abstract: Highlights: Compression properties of porcupine's quill (PQ) are obtained and compared with literature and analytical solutions. X-ray Computed Tomography is utilised to quantify the micro-structures of porcupine's quill before and after experiments. Key micro architectural features of PQ are presented and mimicked using Voronoi lattice design framework. Key design parameters for mimicked PQ include density, Voronoi's seed arrangement and number of axial symmetrical segments. Various designs are 3D printed using stereolithography (SLA) method. Abstract: A porcupine's quill is an extraordinary natural armor capable of withstanding high compression load. By unravelling the unique properties of the porcupine quill design, the bioinspired structures can be applied in engineering applications. The present work investigates both the mechanical and chemical properties of a porcupine quill. An axial compression test is conducted on the natural material in three states: the entire composite quill structure and the response of shell and foam phases individually. These mechanical responses are reported, and compressive failure modes are quantified by scanning electron microscopy (SEM) and micro-computed tomography (µCT). Fourier-transform infrared (FTIR) spectroscopy is conducted and a slight compositional variation is found between the shell and foam phases of the porcupine quill. The design of a porcupine quill inspired structure is achieved through fabrication by stereolithography (SLA) additive manufacturing (AM) technology. Based on these design workflows, the properties of the structures, including struts length and relative density are analysed. Random workflow has a higher number of short struts while longer struts dominate reflected workflow. Relative density increases with the increasing number of seeds. However, it decreases with a growing number of sectors. Qualitative analysis of the numerical simulation presented shows the importance of struts connectivity for efficient stress distribution.